Synergistic Cytotoxicity of Methyl 4-Hydroxycinnamate and Carnosic Acid to Acute Myeloid Leukemia Cells via Calcium-Dependent Apoptosis Induction - Trachtenberg, Aviram; Muduli, Suchismita; Sidoryk, Katarzyna; Cybulski, Marcin; Danilenko, Michael (Frontiers in Pharmacology, 2019)
Acute myeloid leukemia (AML) is a malignant hematopoietic disease with poor prognosis for most patients. Conventional chemotherapy has been the standard treatment approach for AML in the past 40 years with limited success. Although, several targeted drugs were recently approved, their long-term impact on the survival of patients with AML is yet to be determined. Thus, it is still necessary to develop alternative therapeutic approaches for this disease. We have previously shown a marked synergistic anti-leukemic effect of two polyphenols, curcumin (CUR) and carnosic acid (CA), on AML cells in-vitro and in-vivo. In this study, we identified another phenolic compound, methyl 4-hydroxycinnamate (MHC), which among several tested phytochemicals could uniquely cooperate with CA in killing AML cells, but not normal peripheral blood mononuclear cells. Notably, our data revealed striking phenotypical and mechanistic similarities in the apoptotic effects of MHC+CA and CUR+CA on AML cells. Yet, we show that MHC is a non-fluorescent molecule, which is an important technical advantage over CUR that can interfere in various fluorescence-based assays. Collectively, we demonstrated for the first time the antileukemic activity of MHC in combination with another phenolic compound. This type of synergistically acting combinations may represent prototypes for novel antileukemic therapy.